2018
DOI: 10.15761/crt.1000232
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation confers clinical potential to predict the oral cancer prognosis

Abstract: Background: Patient understanding is a fundamental requirement for the consent process, yet current UK Department of Health consent forms rely on handwritten explanations on admission prior to cardiac surgery. A pre-printed consent form containing pertinent information about the planned procedure and its associated benefits/risks may benefit in patient retention of information.Trial design: Randomised study using a pre-test/post-test design in which participants completed a questionnaire prior to providing con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Therefore, DNA methylation analysis using buccal smear samples may be used as a molecular screen for oral cancer, particularly in areas with limited resources. A few previous studies investigated interactions between BQ chewing habits and DNA methylation using smear samples from buccal OSCC [8,31]. However, our study is the first report that shows increased levels of DNA methylation in healthy buccal mucosa samples obtained from BQ chewers.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, DNA methylation analysis using buccal smear samples may be used as a molecular screen for oral cancer, particularly in areas with limited resources. A few previous studies investigated interactions between BQ chewing habits and DNA methylation using smear samples from buccal OSCC [8,31]. However, our study is the first report that shows increased levels of DNA methylation in healthy buccal mucosa samples obtained from BQ chewers.…”
Section: Discussionmentioning
confidence: 72%
“…The association between DNA methylation and carcinogenesis has been widely investigated (Asokan et al, 2014; Cheng et al, 2016, 2017, 2018; Kan et al, 2014; Locke et al, 2019; Sharma et al, 2010; Song et al, 2017; Ushijima, 2005; Yang et al, 2018). Several methylated genes have been reported as biomarkers for the detection of precancers, cancers, or disease recurrence or for monitoring therapeutic efficacy, with some of them having been approved as in vitro diagnostic devices (Locke et al, 2019; Song et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that hypermethylation of PAX1 and ZNF582 was associated with OSCC occurrence. Studies using 43 tumor tissues and 42 non‐cancerous matched tissues reported that high methylation levels of both genes in tumors were more commonly observed in poor prognosis patients 13 . However, the correlation between hypermethylation and severity among OSCC patients has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc finger protein 582 (ZNF582) , located at chromosome 19q13.43, is a zinc finger protein containing one KRAB‐AB domain and nine zinc finger motifs, 11 which affect cell differentiation, cell proliferation, apoptosis, and neoplastic transformation 12 . PAX1 and ZNF582 hypermethylation was found in oral cancer and cervical cancer 13,14 . In particular, several studies in Taiwan suggested that methylation of PAX1 and ZNF582 is potential biomarkers for OSCC detection 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation